Impact of beta-blocker usage on delirium in patients with sepsis in ICU: a cross-sectional study - Ouyang, Honglian; Wang, Xiaoqi; Deng, Dingwei; Wang, Qianqian; Yu, Yi (Frontiers in Medicine, 2024)
Delirium in patients with sepsis can be life-threatening. This study aims to investigate the impact of the use of beta-blockers on the occurrence of delirium in patients with sepsis in the ICU by utilizing a comprehensive dataset. This is a cross-sectional study conducted using the data obtained from a single ICU in the USA. Patients diagnosed with sepsis and receiving beta-blockers were compared with those not receiving beta-blockers. Propensity score matching (PSM) and multiple regression analysis were employed to adjust for potential confounders. Among the 19,660 patients hospitalized for sepsis, the beta-blocker and non-user groups comprised 13,119 (66.73%) and 6,541 (33.27%) patients, respectively. Multivariable logistic regression models revealed a significant reduction of 60% in 7-day delirium for beta-blocker users (OR = 0.40, 95% CI: 0.37-0.43, P < 0.001), for 30-day delirium (OR = 0.32, 95% CI: 0.29-0.35, P < 0.001), and for 90-day delirium (OR = 0.33, 95% CI: 0.30-0.35, P < 0.001). The PSM results further strengthen the validity of these findings. An analysis of safety issues demonstrated that beta-blockers may have an impact on the risk of acute kidney injury. However, following PSM, the results are not considered robust. Furthermore, there was no discernible change in the odds of renal replacement therapy and the length of ICU stays. Our findings suggest a potential protective effect of beta-blockers against delirium in patients with sepsis.Nevertheless, the observational design limits causal inference, necessitating future randomized controlled trials to validate these findings.